2023
DOI: 10.30574/wjarr.2023.17.1.1446
|View full text |Cite
|
Sign up to set email alerts
|

Health care outcomes due to incidents of burnout in Asia: A literature review

Abstract: Introduction: Stress is a part of life that is considered one of the great pandemics of the 21th century. At work, stress can affect health, personal well-being and job satisfaction, and in severe cases can trigger burnout syndrome. Factors that cause burnout including personal factors, workload excessive, and the quality of the work environment that do not support. Methods: This research uses literature study design from an international database, namely PubMed with the keywords used "burnout", "health worker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Burnout syndrome has a significant relationship with nurses' workload (p-value = 0.005), and high workload specifically affects one of burnout syndrome dimensions such as physical and emotional exhaustion [18]. Previous research has consistently found the disadvantages of job characteristics, such as high workload, long shifts, low control self-esteem, low staffing levels, low schedule flexibility, low various task, negative relationship among health workers, time pressure, work and psychological demands, poor support and leadership, role conflict , negative team relations, and job insecurity [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Burnout syndrome has a significant relationship with nurses' workload (p-value = 0.005), and high workload specifically affects one of burnout syndrome dimensions such as physical and emotional exhaustion [18]. Previous research has consistently found the disadvantages of job characteristics, such as high workload, long shifts, low control self-esteem, low staffing levels, low schedule flexibility, low various task, negative relationship among health workers, time pressure, work and psychological demands, poor support and leadership, role conflict , negative team relations, and job insecurity [19,20].…”
Section: Discussionmentioning
confidence: 99%